Reciprocity of thermal diffusion in time-modulated systems - Li, Jiaxin; Li, Ying; Cao, Pei-Chao; Qi, Minghong; Zheng, Xu; Peng, Yu-Gui; Li, Baowen; Zhu, Xue-Feng; Alù, Andrea; Chen, Hongsheng; Qiu, Cheng-Wei (Nature communications, 2022)
The reciprocity principle governs the symmetry in transmission of electromagnetic and acoustic waves, as well as the diffusion of heat between two points in space, with important consequences for thermal management and energy harvesting. There has been significant recent interest in materials with time-modulated properties, which have been shown to efficiently break reciprocity for light, sound, and even charge diffusion. However, time modulation may not be a plausible approach to break thermal reciprocity, in contrast to the usual perception. We establish a theoretical framework to accurately describe the behavior of diffusive processes under time modulation, and prove that thermal reciprocity in dynamic materials is generally preserved by the continuity equation, unless some external bias or special material is considered. We then experimentally demonstrate reciprocal heat transfer in a time-modulated device. Our findings correct previous misconceptions regarding reciprocity breaking for thermal diffusion, revealing the generality of symmetry constraints in heat transfer, and clarifying its differences from other transport processes in what concerns the principles of reciprocity and microscopic reversibility. The use of time modulation to break reciprocity is well understood for light, sound or charge diffusion, but it’s unclear whether it can work for thermal diffusion. Here, the authors answer in the negative by analysing diffusive processes under time modulation, and giving numerical and experimental evidence.